ANALISIS KELAYAKAN USAHA PENGGILINGAN PADI KELILING DI KAMPUNG PRAFI MULYA KABUPATEN MANOKWARI - Nurma Fitriani; Wambrauw, Ludia; Fenetiruma, Obadja Andris (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2023)
The mobile rice milling business has quite a significant potential because technology and science continue to develop, producing innovations to make human work more accessible. This research aims to analyze the feasibility of a mobile rice milling business in Prafi Mulya Village, Prafi District, Manokwari Regency. As a case study, the research method used is a quantitative descriptive method using tabulation and simple mathematics with mobile rice mill entrepreneurs in Prafi Mulya Village, Manokwari Regency. Data analysis uses Internal Rate of Return (IRR), Net Present Value (NPV), and RC-Ratio (RCR) analysis. The research results show that the mobile rice milling business has a minimum income of IDR 16,315,,667 and the maximum income is IDR 212,790,381 with an average income of IDR 66,323,683 per year. Furthermore, the average IRR value is 7%, and the average NPV value is IDR 894,170,337.00 and the average RCR value is 2.03. The mobile rice milling business in Prafi Mulya Village, Prafi District, Manokwari Regency, is included in the suitable business or running criteria. This is because the calculation results based on the NPV and RCR assessment criteria show that the rice milling business has met the business feasibility requirements. Still, based on the IRR, three respondents are in the no category because the IRR value is smaller than the discount rate.